Assessing recent increases in cash demand - Clemens Jobst; Helmut Stix (Deutsche Bundesbank, 2017)
Contrary to predictions that demand for cash will decline with the increased availability and use of non-cash payment means, currency demand has increased in the Euro area and the US over the past 15 years. Against this background, this short article summarizes recent findings from Jobst and Stix (2017), who provide a discussion of trends in currency demand, and presents additional descriptive evidence. In a first step, currency demand over a longer period is analyzed for the USA, Germany and the Euro area. This is helpful for understanding and assessing recent trends. In a second step, evidence from 70 economies is analyzed for the period from 2001 to 2014. This broader perspective informs us about the development for currencies that do not circulate internationally. Our descriptive account provides several insights: (i) Recent increases for the euro and the US dollar are strong even if seen over a 100 year horizon. (ii) Over the period from 2001 to 2014 currency demand has increased in many economies. (iii) In economies where currency demand increased, the increase typically happened after the start of the economic and financial crisis of 2007/08. What are the drivers of recent increases in currency demand? Jobst and Stix (2017) estimate panel money demand models, accounting for changes in GDP, interest rates and shadow economic activities. In economies with high GDP, a substantial share of the increase cannot be explained by changes in interest rates or in the size of the shadow economy. We conjecture that the unexplained component is related to increased hoarding.
Keywords: 330